Cognitive Methods in Social Psychology - Klauer, Karl Christoph (EBL-Schweitzer, 2011)
Cover; Front Matter; Contents; Introduction--Cognitive Methods in Social Psychology: Inferring Latent Processes; 1--The Assessment of Human Attention; 2--The Sequential Priming Paradigm: A Primer; 3--Response Interference Tasks as Indirect Measures of Automatic Associations; 4--Evaluative Conditioning: Methodological Considerations; 5--Working Memory Capacity in Social Psychology; 6--Psycholinguistic Methods in Social Psychology; 7--Metacognition: Methods to Assess Primary versus Secondary Cognition; 8--Peripheral Psychophysiological Methods